1998
DOI: 10.1046/j.1523-1747.1998.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation Induced Suppression of Mantoux Reactions in Humans

Abstract: The effects of low dose ultraviolet (UV) radiation on delayed type hypersensitivity responses to tuberculin purified protein derivative were investigated in 17 healthy, Mantoux-positive volunteers. Suberythemal and erythemal doses of solar simulated UV from a fluorescent lamp source were delivered to the subjects' lower backs daily for five consecutive days. Mantoux testing with intradermally injected purified protein derivative was then performed at both the irradiated sites and an adjacent, unirradiated site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 11 publications
5
51
1
Order By: Relevance
“…This difference was statistically significant. A similar result was obtained by Moyal, 5 Kuchel, 6 Damian 8 and Wammanda 10 et al when they examined Mantoux induration measurements without a set cutoff point. Since the Mantoux tests on the inner thigh and the volar surface of the forearm were concurrently applied, the most likely explanation for this observed difference would be the presence of a factor that could negatively influence the delayed type of hypersensitivity reaction in the children in a differential way.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This difference was statistically significant. A similar result was obtained by Moyal, 5 Kuchel, 6 Damian 8 and Wammanda 10 et al when they examined Mantoux induration measurements without a set cutoff point. Since the Mantoux tests on the inner thigh and the volar surface of the forearm were concurrently applied, the most likely explanation for this observed difference would be the presence of a factor that could negatively influence the delayed type of hypersensitivity reaction in the children in a differential way.…”
Section: Discussionsupporting
confidence: 79%
“…3,4 Immunosupression induced by ultraviolet rays (UVR) has been shown to alter the skin response to the Mantoux test negatively. [5][6][7][8][9] Furthermore, It has been observed that even modest doses of UV rays can significantly reduce local delayed type IV hypersensitivity (DTH) response to recall antigens, and that recent sun exposure should be considered a possible cause of false negative Mantoux response. 5 Kuchel and Barnetson 8 documented a clear reduction in the Mantoux response at UV irradiated site when compared to the un-irradiated site.…”
Section: Introductionmentioning
confidence: 99%
“…Recent photoimmunologic work shows that UVR downregulates cellular immunity (Damian et al 1998;Kelly et al 1998), attenuating T-helper (Th)1 Tcell-mediated immune responses . These responses are thought to be significantly involved in some autoimmune disorders such as MS, type 1 diabetes, and RA (Mackay 2000).…”
mentioning
confidence: 99%
“…The Mantoux reaction is used clinically to assess previous exposure to Mycobacterium tuberculosis or the Bacille Calmette Guerin vaccine, and has been used previously in our laboratory as a model of UV immunosuppression in humans [5,6].…”
mentioning
confidence: 99%